The Power of Digital Persuasion: Examining the Impact of Influencers and Content Marketing on Purchase Decisions - Refi Royadi; Syaipul Ramdhan; Yunitasari Amaludin (Al-Qalam Institue, 2026)
This study aims to examine the influence of influencer marketing and content marketing on consumer purchase decisions for Jims Honey products in the digital era. The research employs a quantitative explanatory approach with a sample of 100 respondents selected through purposive sampling, consisting of consumers who follow Jims Honey’s social media accounts and have previously made a purchase. Data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, as well as t-tests and F-tests. The findings reveal that influencer marketing has a significant positive effect on purchase decisions (β = 0.678; p < 0.001), while content marketing also significantly influences purchase decisions (β = 0.434; p < 0.001). Simultaneously, both variables demonstrate a significant effect (F = 83.366; p < 0.001), with a coefficient of determination (R² = 0.629), indicating that 62.9% of the variance in purchase decisions is explained by the two independent variables. These results imply that businesses in the digital marketplace should strategically integrate influencer partnerships and high-quality content marketing to strengthen consumer engagement and enhance purchase decision outcomes.